2022
DOI: 10.1108/pr-09-2020-0706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perceived organisational politics and effort–reward imbalance on work outcomes – the moderating role of mindfulness

Abstract: Purpose The purpose of this study is to examine the moderating effects of mindfulness on the relationships between work stressors (perceived organisational politics [POP] and effort–reward imbalance [ERI]) and work outcomes (job burnout [JBO] and job satisfaction [JS]).Design/methodology/approach Time-lagged data were collected from public sector employees in France and Pakistan. The final samples (France, N = 204; Pakistan, N = 217) were tested using multiple moderating regression.Findings Mindfulness moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…The sample item included in this scale, “when it comes to pay rise and promotion decisions, policies are irrelevant.” The combined Cronbach alpha for this scale was 0.93. Moreover, this scale has high internal consistency, most frequently used in existing studies across different organizational contexts (Murtaza et al ., 2022; Cheong and Kim, 2022; AL-Abrrow, 2022; Atta and Khan, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The sample item included in this scale, “when it comes to pay rise and promotion decisions, policies are irrelevant.” The combined Cronbach alpha for this scale was 0.93. Moreover, this scale has high internal consistency, most frequently used in existing studies across different organizational contexts (Murtaza et al ., 2022; Cheong and Kim, 2022; AL-Abrrow, 2022; Atta and Khan, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with COR theory, individual personal resources are depleted in dealing with the stressor, which leaves limited resources available for work demands (Hobfoll, 2011). This resource loss can lead to emotional exhaustion (Murtaza et al, 2022). Accordingly, we predict that the relationship between NWG and emotional exhaustion will strengthen in case of SM usage is high in the workplace because the exposure of (mis)information (among SM friends) as a stressor can cause strain (First et al, 2021; Wolfers & Utz, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Many researchers postulated that POP has mainly negative consequences as discussed by Li et al, (2013) politics in the organization brings lot of uncertainties and risks. Efforts to cope with political situation results in depletion of emotional resources thus exhausting a person emotionally (Karatepe & Karatepe, 2009;Maslach & Goldberg 1999;Murtaza et al, 2022). Goodman and Boss (2002) as well as Harris et al (2005) found emotional exhaustion to be one of the basic stress related outcomes of POP.…”
Section: Perceived Organizational Politics (Pop) and Emotional Exhaus...mentioning
confidence: 99%